Blurred Molecular Epidemiological Lines Between the Two Dominant Methicillin-Resistant Staphylococcus aureus Clones. (27th June 2019) - Dupper, Amy C; Sullivan, Mitchell J; Chacko, Kieran I; Mishkin, Aaron; Ciferri, Brianne; Kumaresh, Ajay; Berbel Caban, Ana; Oussenko, Irina; Beckford, Colleen; Zeitouni, Nathalie E; Sebra, Robert; Hamula, Camille; et al.
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) causes life-threatening infections in both community and hospital settings and is a leading cause of health care–associated infections (HAIs). We sought to describe the molecular epidemiological landscape of patients with MRSA bloodstream infections (BSIs) at an urban medical center by evaluating the clinical characteristics associated with the two dominant endemic clones. Methods: Comprehensive clinical data from the electronic health records of 227 hospitalized patients ≥18 years old with MRSA BSI over a 33-month period in New York City were collected. The descriptive epidemiology and mortality associated with the two dominant clones were compared using logistic regression. Results: Molecular analysis revealed that 91% of all single-patient MRSA BSIs were due to two equally represented genotypes, clonal complex (CC) 5 (n = 117) and CC8 (n = 110). MRSA BSIs were associated with a 90-day mortality rate of 27%. CC8 caused disease more frequently in younger age groups (56 ± 17 vs 67 ± 17 years old; P < .001) and in those of nonwhite race (odds ratio [OR], 3.45; 95% confidence interval [CI], 1.51–7.87; P = .003), with few other major distinguishing features. Morbidity and mortality also did not differ significantly between the two clones. CC8 caused BSIs more frequently in the setting of peripheral intravenous catheters (OR, 5.96; 95% CI, 1.51–23.50; P = .01). Conclusions: The clinical features distinguishing dominant MRSA clones continue to converge. The association of CC8 with peripheral intravenous catheter infections underscores the importance of classical community clones causing hospital-onset infections. Ongoing monitoring and analysis of the dynamic epidemiology of this endemic pathogen are crucial to inform management and prevent disease.